A newer technique to program a semi adjustable articulator - R Venkateshwaran; Suma Karthigeyan; P S Manoharan; Jagadish Konchada; Manikandan Ramaswamy; Bhuminathan (Wolters Kluwer Medknow Publications, 2014)
Introduction: The difficulty in reproducing accurate angle of condylar guidance in semi-adjustable articulators. Purpose: The purpose of this study was to determine the correlation between the angle of horizontal condylar inclination obtained on a semi-adjustable articulator and the corresponding angle traced on a temporomandibular joint (TMJ) radiograph in completely edentulous subject. Materials and Methods: The horizontal condylar inclination angle was obtained in a semi-adjustable articulator by means of height tracer (extra oral tracing device) and interocclusal records to program the articulator in 21 subjects. TMJ radiograph were recorded by the same operator with same orthopantomogram (OPG) machine (planmeca). Tracings of inclines of articular eminence on the radiograph were compared with the angle obtained on a semi-adjustable articulator. Each measurement was made using manual methods of measuring angle. The results were subjected to the Pearson correlation statistical analysis (α =0.01). Results: The outline of the articular eminence in a TMJ tomogram radiographic image was identified and traced. A significant correlation was found between the horizontal condylar inclination on a semi-adjustable and the corresponding TMJ tomogram radiographic image for both right (R = 0.789; P = 0.001) and left (i = 0.747; P = 0.004) sides. Conclusion: The articular eminence traced on a TMJ tomogram image represents the horizontal condylar inclination with a mean difference of 5° in 21 subjects evaluated.